USO DE TECNOLOGIAS DIGITAIS NA EDUCAÇÃO INFANTIL EM MOVIMENTOS DE UMA CULTURA MAKER - CLEIDE MARIA DOS PASSOS ARRUDA (2024)
This research, attached to the Education Postgraduate Program of the Federal University of Mato Grosso do Sul (PPGEdu/UFMS) and the Technology and Mathematics Education Study Group/UFMS (GETecMat), has the aim of analyze a Maker Culture approach with the use of Digital Technologies with children in Early Childhood Education. The studies were carried out in partnership with an Early Childhood Education teacher, who works with children about 4 years old, in a public school in the municipality of Campo Grande/MS. To produce the research data actions were carried out at the school in partnership with the teacher: study of the prescribed curriculum and planning with the teacher; observation of classes; meetings to evaluate the actions at the school. These actions were recorded on video, audio or images/photographs and, thus, the data for this research was constituted. The data is presented in this dissertation in narratives, guided by the actions developed at the school and studies on integrating digital technologies into the school curriculum, Maker Culture and the constructionist approach. We started from information given by the partner teacher that she had no theoretical knowledge, nor did her practice use digital technologies or maker culture with her students. Based on this fact and the studies carried out, we believe that in these research projects and in the partnership between the researchers and the teacher, the use of Digital Technologies was carried out in movements of a maker culture and with the aim of integrating it into the school curriculum, according to the narratives presented in this research report.